2019
DOI: 10.1093/cdn/nzz034.p10-100-19
|View full text |Cite
|
Sign up to set email alerts
|

Calcium to Magnesium Ratio Higher Than Optimal Across Age Groups (P10-100-19)

Abstract: Objectives The ratio of calcium to magnesium (Ca: Mg) intake has gained immense attention in recent years, since a ratio above 2:1 has been associated with increased risk of metabolic, inflammatory and cardiovascular disorders. The objective of this study was to assess Ca: Mg ratios across age groups and to determine the relationship between Ca: Mg ratios and markers of inflammation. Methods Adult men and women, 18 to 60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Ca/Mg ratio was 1.18 almost similar to the recommended value of 1.0 [46] lower than the range of 1.70 -2.5 recommended to reduce the risk of cancer [47] and associated with greater inflammation [48]. This allows us to say that B. aegyptiaca seed oil would reduce the risk of inflammation.…”
Section: Mineral Compositionsupporting
confidence: 53%
“…The Ca/Mg ratio was 1.18 almost similar to the recommended value of 1.0 [46] lower than the range of 1.70 -2.5 recommended to reduce the risk of cancer [47] and associated with greater inflammation [48]. This allows us to say that B. aegyptiaca seed oil would reduce the risk of inflammation.…”
Section: Mineral Compositionsupporting
confidence: 53%
“…The results also showed a considerable amount of macrominerals in the algal constitution. Ca and Mg were determined at 9.56 g/kg dw and 11.96 g/kg dw, respectively, deviating from the 2:1 ratio described as optimal for osteoporosis prevention [23]. Ca values are reported to be as high as 69.6 g/kg, and magnesium reaches 15.5 g/kg in this alga [17], highlighting the potential of this species as a source of these nutrients.…”
Section: Resultsmentioning
confidence: 72%
“…The ratio of Calcium to Magnesium intake has gained attention in recent years. Deluccia et al [65] reported that a ratio above 2:1 has been associated with increased risk of metabolic, inflammatory and cardiovascular disorder. The Ca/Mg ratio of the selected vegetables is in order and could not cause any harm to the consumer.…”
Section: Mineral Ratiomentioning
confidence: 99%